Akreditasi Sekolah: Faktor Penyebab Rendahnya Peringkat Akreditasi Sekolah Dasar - Arismunandar Arismunandar; Sumarlin Mus (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
The low accreditation ranking of Muhammadiyah elementary schools in Makassar City indicates a systemic problem in meeting national education quality standards. This study aims to identify the factors causing the low accreditation based on core performance components and relative fulfillment indicators in the IASP2020 accreditation system. This study uses a descriptive qualitative approach with a multi-case study design in three Muhammadiyah elementary schools, as well as data collection techniques through field observations, in-depth interviews, and official school documentation. The data obtained were analyzed using the Miles and Huberman interactive model to gain a comprehensive contextual understanding. The results of the study indicate that the low quality of teachers, the mismatch between educational background and the subjects taught, and the weak implementation of school management functions are the main factors causing the low accreditation. In addition, it was found that school self-evaluation is still administrative in nature and has not been used as a basis for continuous quality development. This study suggests the need for comprehensive intervention through teacher competency improvement programs, principal leadership training, and reformulation of the internal quality assurance system based on real performance according to the IASP2020 principles.